PENGARUH SYSTEM SELF ASSESMENT TERHADAP KINERJA PEGAWAI PAJAK (STUDI KASUS PADA KANTOR PELAYANAN PAJAK KPP KEBAYORAN BARU TIGA JAKARTA SELATAN) - SARI, TINI DITA; HERIANTI, EVA (Prosiding Seminar Nasional INDOCOMPAC)
This study aimed to axamine the effect of the system of self assesment of the performance tax. Samples in this study were fifty respondents in Kantor Pelayanan Pajak (KPP) Pratama Kebayoran Baru Tiga. The results in this study were collected through questionnaires were processed and analyzed using multiple linear regression. The sampling method used was probability sampling. Based on the results of research that has been done in the statistical test that calculates positive and significant impact on the performance because the tax thitung 2,273 ttable value of 2,0086 rounded to 2,009 (2,273 > 2,009) and a significantly smaller value of 0,028 < 0,05. Meanwhile, the variable pay not significantly affect the performance of the tax, because thitung 975 ttable value of 2,0086 rounded to 2,009 (975 < 2,009) and the value significantly greater than (0,047 < 0,05). And variable reported positive and significant impact on the performance of the tax, because thitung 2,036 > value ttabel 2,0086 rounded to 2,009 and the value significantly greater than 0,335 > 0,05. And calculate, pay and report positive and significant impact on the performance of the tax because the value fhitung 9,138 > value ftable 3,18 (9,138 > 3,18) and significant value of 0,000 is smaller than the value of the real level of 0,05 (0,000 < 0,05).